El concepto de negritud en el ensayo de Adalberto Ortiz (Crítica) - Montaño Paredes, Joshua (2024)
This work is an effort to present, in a contextualized manner, Adalberto Ortiz’s reflections on negritude. In order to achieve this, this paper starts by introducing antecedents from literary studies dedicated to the author, and from Ortiz’s life and works as well, that explain the emergence of his essays on negritude. Now on the subject, a description of Ortiz’s essays on negritude is given and they are debated with essays by relevant cultural theorists. Finally, an account is given of the main findings of the proposed analysis.